Using ecological momentary assessment to track how contemplative mental training is implemented into everyday life. (September 2021) - Linz, R.; Engert, V.; Singer, T.
Abstract : Scientific investigations of the effects of meditation-based mental training are increasingly relying on studies in naturalistic settings. Ecological momentary assessment (EMA) approaches are well-suited to explore training-induced mental states (i.e., affect, thought content, stress experience), and the degree to which training effects carry over to practitioners' daily routines. We will present findings from the ReSource Project, a large-scale, longitudinal 9-month mental training study. We compared results from an EMA study (N=289) with previous ReSource findings on stress, affect and thought content, which were gathered using complementary methods (retrospective assessments, acute stress in the TSST, and acute practice effects (pre vs. post meditation session). While our findings corroborate prior evidence suggesting differential effects of distinct mental training modules on arousal states and present-moment focus, effects on acute stress reactivity and associated cortisol levels did no translate to ecological contexts. Together, our results suggest partial overlap regarding presence-focus and arousal, but an overall limited generalizability of mental training effects from acute laboratory stress to individuals' daily lives.